(untitled) (Revista de História Regional, 2007)
This article tries to read a singular document: the Programma Histórico by José Feliciano Fernandes Pinheiro, Viscount of São Leopoldo, published in 1839. Representative of an idea of history which was becoming consolidated in Brazil, the document - seen as part of a founding discourse on national historiography, allows us to think about the possible dialogues between hsitory and discourse analysis, as well as to reflect on the construction on historiographical discourse itself.